Formulation and evaluation of solid self micro emulsifying drug delivery system using aerosil 200 as solid carrier - Bhagwat, Durgacharan Arun; DSouza, John Intru (International Current Pharmaceutical Journal, 2012)
Improvement of bio-availability of poorly water soluble drugs presents one of the furthermost challenge in drug formulations. One of the most admired and commercially viable formulation approach for this challenge is solid self micro emulsifying drug delivery system (S-SMEDDS). There are many techniques to convert liquid SMEDDS to solid, but an adsorption technique is simple and economic. Hence aim of present study was to develop S-SMEDDS of poorly water soluble drug Telmisartan (TEL) using Aerosil 200 as solid carrier. Liquid SMEDDS was prepared using Acrysol EL 135, Tween 80 and PEG 400 as oil, surfactant and co-surfactant and was converted to S-SMEDDS by adsorbing it on Aerosil 200. Prepared S-SMEDDS was evaluated for flow properties, drug content, reconstitution properties, DSC, SEM, in-vitro drug release and ex-vivo intestinal permeability study. Results showed that prepared S-SMEDDS have good flow property with 99.45 ± 0.02% drug content. Dilution study by visual observation showed that there was spontaneous micro emulsification and no sign of phase separation. Droplet size was found to be 0.34 µm with polydispersity index of 0.25. DSC thermogram showed that crystallization of TEL was inhibited. SEM photograph showed smooth surface of S-SMEDDS with less aggregation. Drug releases from S- SMEDDS were found to be significantly higher as compared with that of plain TEL. Ex-vivo intestinal permeability study revealed that diffusion of drug was significantly higher from S-SMEDDS than that of suspension of plain TEL. Study concluded that S-SMEDDS can effectively formulated by adsorption technique with enhanced dissolution rate and concomitantly bioavailability. DOI: http://dx.doi.org/10.3329/icpj.v1i12.12451 International Current Pharmaceutical Journal 2012, 1(12): 414-419